Steinalderen i Sørøst-Norge Faglig program for steinalderundersøkelser ved Kulturhistorisk museum - Damlien, Hege (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2021)
The Stone Age in Southeastern Norway. The Academic Program for Stone Age Research at the Museum of Cultural History comprises a general overview of excavations, carried out between 2000-2017, of 430 sites, graves, depots, hunting pits and other sites, and presents a broad and updated report on the status of research relating to the Stone Age (c. 9500-1700 BC) in the region.Insufficient knowledge has been the impetus for identification of four main areas for concerted prospective effort:• Technology• Settlement and land use• Subsistence and economy• Rituals and their practiceAlso presented in this program for Stone Age research are concrete strategies and initiatives that will contribute to filling in these knowledge gaps, advancing the field, and laying foundations for further research.The Stone Age in Southeastern Norway has been written with researchers, managers of cultural heritage and students in mind, as well as all others interested in a deep dive into our earliest history. This book will be an important reference for planning and carrying out future Stone Age excavations under the museum's aegis. It will also serve as a foundation for guidelines the museum provides regarding conservation of our oldest cultural heritage.; Steinalderen i Sørøst-Norge. Faglig program for steinalderundersøkelser ved Kulturhistorisk museum inneholder en helhetlig oversikt over utgravinger av 430 boplasser, begravelser, depoter, fangstanlegg m.m. fra år 2000 til 2017, og presenterer en bred og oppdatert redegjørelse for forskningsstatus knyttet til steinalderen (ca. 9500-1700 f.Kr.) i regionen.I presentasjonen av forskningsstatus synliggjøres ikke bare det vi vet per i dag, men også betydelige kunnskapshull. Den manglede kunnskapen har dannet utgangspunkt for formuleringen av fire framtidige satsingsområder:- Teknologi- Bosetning og landskapsbruk- Ressursgrunnlag og økonomi- Ritualer og ritualisert praksisI dette faglige programmet for steinalderundersøkelser presenteres konkrete forslag til strategier og tiltak som vil bidra til å tette disse kunnskapshullene, skape faglig utvikling og danne grunnlag for videre forskning.Steinalderen i Sørøst-Norge er skrevet for forskere, forvaltere, studenter og andre som vil gjøre dypdykk i vår eldste forhistorie. Boken vil være et viktig verktøy for planlegging og gjennomføring av kommende steinalderutgravninger ved Kulturhistorisk museum. Den vil også danne et grunnlag for de rådene museet gir i forbindelse med forvaltningen av våre eldste kulturminner.